ANALISIS PEMANFAATAN AIR HUJAN SEBAGAI AIR BAKU DENGAN SISTEM PEMANENAN AIR HUJAN - Ustrati, Fauziah; Hisyam, Endang S; Sandy, Boy Dian Anugra (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2023)
ABSTRACT: A Based on the Regulation of the State Minister for the Environment No. 12 of 2009, it is explained that rainwater is a source of water that can be used as a filler for groundwater and or used directly to overcome water shortages during the dry season and floods during the rainy season. The construction of a new building for the Rectorate of the University of Bangka Belitung resulted in a change in land use, which previously was a forest that was still overgrown with plants into a building to support lecture activities. This will have an impact on decreasing the quantity of water that seeps into the ground and increasing runoff. One of the water conservation technologies that can be used to utilize rainwater is rainwater harvesting. The existence of management and utilization of rainwater can reduce surface runoff discharge and continuous use of groundwater. Therefore, rainwater harvesting is carried out as an appropriate water conservation technology to be applied at the Rectorate Building of the University of Bangka Belitung which is expected to save groundwater use and reduce surface runoff discharge. The method used is the method of collecting and processing data. In the analysis of Rainwater Harvesting (RH), the calculation of RH capacity is calculated based on the Minister of Public Works Regulation concerning Implementation of Non-Pipeline Road Network SPAM Development No. 01/PRT/M2009. From the research results, it was found that the raw water requirement for the Rector Building at the University of Bangka Belitung was 2.275 m3/day with a PAH tank capacity of 76 m3 and the total cost of building a rainwater reservoir for the Rector Building at the University of Bangka Belitung was Rp. 147,453,000.00.. Keywords: Rainwater, Raw Water, Rainwater StorageABSTRAK: Berdasarkan Peraturan Menteri Negara Lingkungan Hidup No 12 tahun 2009, dijelaskan bahwa air hujan merupakan sumber air yang dapat dimanfaatkan sebagai pengisi air tanah dan atau dimanfaatkan secara langsung untuk mengatasi kekurangan air pada musim kemarau dan banjir pada musim penghujan. Adanya pembangunanan gedung baru Rektorat Universitas Bangka Belitung mengakibatkan berubahnya tata guna lahan, yang sebelumnya kawasan tersebut adalah hutan yang masih ditumbuhi tanaman menjadi gedung untuk menunjang aktivitas perkuliahan. Hal ini akan berdampak pada menurunnya kuantitas air yang meresap ke dalam tanah dan meningkatnya aliran permukaan. Salah satu teknologi konservasi air yang dapat dilakukan untuk memanfaatkan air hujan adalah pemanenan air hujan. Adanya penggelolaan dan pemanfaatan air hujan dapat menggurangi debit aliran permukaan dan penggunaan air tanah secara terus menerus. Oleh karena itu dilakukannya pemanenan air hujan sebagai teknologi konservasi air yang tepat guna untuk diaplikasikan di Gedung Rektorat Universitas Bangka Belitung yang diharapkan dapat menghemat penggunaan air tanah dan mengurangi debit limpasan aliran permukaan. Metode yang digunakan yaitu metode pengumpulan dan pengolahan data. Dalam analisis kapasitas Pemanenan Air Hujan (PAH), perhitungan kapasitas PAH dihitung berdasarkan Permen PU tentang Penyelenggaraan Pengembangan SPAM Bukan Jaringan Jalan Perpipaan No. 01/PRT/M2009. Dari hasil penelitian, didapatkan kebutuhan air baku pada Gedung Rektorat Universitas Bangka Belitung sebesar 2,275 m3/hari dengan kapasitas tangki PAH sebesar 76 m3serta total biaya pembangunan penampung air hujan Gedung Rektorat Universitas Bangka Belitung sebesar Rp 147.453.000,00.Kata kunci: Air Hujan, Air Baku, Penampungan Air Hujan